Simulating the formation and fate of dense water in a midlatitude marginal sea during normal and warm winter conditions. Issue 2 (20th February 2013) - Querin, Stefano; Cossarini, Gianpiero; Solidoro, Cosimo
Abstract: [1] Dense shelf water production and the deep convection process in the Adriatic Sea are investigated, considering two case studies: the first is representative of the present climatic situation, whereas the second may be expected in a scenario characterized by mild winter conditions over the basin. Dense water production and spreading are studied using a high‐resolution implementation of the Massachusetts Institute of Technology general circulation model that is initialized and forced with realistic conditions. This paper provides qualitative and quantitative information on mass transport, dense water pathways, thermohaline structures, and the mixing properties of the basin. In the northern Adriatic shelf, seawater temperature is the key element for winter dense water production because it contributes more relevantly than salinity in determining density. In the southern Adriatic Sea, a small amount of dense water that cascades directly into the pit can be formed on the narrow western shelf only during cold winter conditions. Moreover, open ocean deepwater formation occurs in the middle of the southern basin. In late winter and spring, although only when winter conditions have been sufficiently cold, northern Adriatic dense shelf water forms a subsurface stream of which the densest part rapidly sinks in the southern pit along the shelf break, whereas its lighter part flows southward and reaches the Otranto Strait. The frequent occurrence of mild winter conditions could lead to lower dense water production, with a reduced dense water flow from the Adriatic Sea to the Ionian Sea and a potential great impact on the eastern Mediterranean thermohaline circulation. Key Points: Dense water formation and fate in a mid‐latitude marginal sea are described The effect of different winter conditions is investigated Mild winter conditions strongly decrease the Adriatic dense water outflow